Tourist Guide Writing Project: Assisting 4C Skills through Project-Based Learning in English for Tourism - Muthia Farida; Niwayan Sukraini (LPPM Universitas PGRI Semarang, 2024)
One of the recommended teaching methods in the Indonesia’s Merdeka Belajar (Freedom to Learn) Curriculum is Project-based Learning (PjBL). This research aims to explore the implementation of PjBL in assisting the students’ 4C skills through a writing project in English for Tourism Class in Indonesia. This research employed a qualitative design to investigate the PjBL implementation by the teacher to the fifth semester students at a Tour Guiding Program. An open-ended questionnaire, interview, and teacher reflective notes were conducted to collect the data. The data analysis included data reading and categorization, data matching, data reduction, data display and interpretation, and drawing conclusions. The results showed that PjBL gave the opportunities to train the students’ 4C skills through group tasks, data collection, presentation, and the tourist spot visit. They also learned to develop an English writing text more meaningfully, and to construct knowledge about tourism from the real-world context. The challenges found were time limitation, student different characteristics, and teacher’s limited experiences. Teachers who are eager to apply PjBL may use this teaching procedure in this research with the considerations of these challenges and classroom needs. Besides, supplementing an observation method and expanding the research scope are recommended for future research